Earlier vs. later time period of COVID-19 infection and emergent autoimmune signs, symptoms, and serologies - Oakes, Emily G.; Dillon, Eilish; Buhler, Katherine A.; Guan, Hongshu; Paudel, Misti; Marks, Kathryne; Adejoorin, Ifeoluwakiisi; Yee, Jeong; Ellrodt, Jack; Tedeschi, Sara; Sparks, Jeffrey; Case, Siobhan M.; et al. (Journal of autoimmunity, 2024)
Autoantibodies and autoimmune diseases after SARS-CoV-2 infection are widely reported. Given evolving variants, milder infections, and increasing population vaccination, we hypothesized that SARS-CoV-2 infection earlier in the pandemic would be associated with more autoimmune connective tissue disease (CTD) symptoms and immunologic abnormalities. Patients ≥18 years old with COVID-19 3/1/2020-8/15/2022 completed the CTD Screening Questionnaire and were tested for 27 autoimmune serologies, SARS-CoV-2 serologies, cell-bound complement activation products (CB-CAPs), and T and B lymphocyte immunophenotypes by flow cytometry. We assessed relationships between symptoms, serologies, and immunophenotypes in earlier (3/1/2020-1/31/2021) vs. later (2/1/2021-8/15/2022) periods, with different predominating SARS-CoV-2 viruses. 57 subjects had earlier and 23 had later pandemic COVID-19. 35 % of earlier vs. 17 % of later pandemic patients had CTD symptoms (p 0.18). More patients were antinuclear antibody (ANA) positive (44 % vs. 13 %, p 0.01) and had lupus anticoagulant (11 % vs. 4 %, p 0.67). After adjustment for age, race, and sex, earlier (vs. later) COVID-19 was associated with increased ANA positivity (OR 4.60, 95%CI 1.17, 18.15). No subjects had positive CB-CAPs. T and B cell immunophenotypes and SARS-CoV-2 serologies did not differ by group. In heatmap analyses, higher autoantibody variety was seen among those with infection in the early pandemic. In this sample, having COVID-19 infection in the earlier (pre-2/1/2021) vs. later pandemic was associated with more CTD symptoms, ANA positivity, and autoantibody reactivities. Earlier SARS-CoV-2 variants circulating in a less vaccinated population with less natural immunity may have been more immunogenic. •SARS-CoV-2 infection in earlier (3/1/2020-1/31/2021) vs. later (2/1/2021-8/15/2022) COVID-19 period was associated with increased ANA positivity, connective tissue disease symptoms, and autoantibody variety.•No increases in relative proportions of four lymphocyte subsets were identified and immunophenotypes were not significantly different in relation to COVID-19 infection period.•The findings suggest that earlier SARS-CoV-2 variants may have been more inflammatory and immunogenic, resulting in autoantibody production.